2014
DOI: 10.1080/00131881.2013.874147
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m teaching, but I’m not really a teacher’. Teaching assistants and the construction of professional identities in Hong Kong schools

Abstract: To cite this article: John Trent (2014) 'I'm teaching, but I'm not really a teacher'. Teaching assistants and the construction of professional identities in Hong Kong schools, Educational Research, 56:1, 28-47, Background: In the past decade, educational settings worldwide have experienced a significant increase in the number of school-based teaching assistants (TAs). The deployment of these TAs has been accompanied by reports of confusion and uncertainty about their roles and responsibilities within schools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…This may be due to the atypical nature of the response which is not generalisable to the wider TA population. Conversely, it may be that published research has not focused on the experiences of TAs, who remain ‘voiceless’, despite repeated calls to address this (Gilbert et al ., ; Roffey‐Barentsen and Watt, ; Trent, ; Lehane, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the atypical nature of the response which is not generalisable to the wider TA population. Conversely, it may be that published research has not focused on the experiences of TAs, who remain ‘voiceless’, despite repeated calls to address this (Gilbert et al ., ; Roffey‐Barentsen and Watt, ; Trent, ; Lehane, ).…”
Section: Resultsmentioning
confidence: 99%
“…Ofsted () raised the first note of caution about TAs’ increasingly direct pedagogical role and suggested that it required investigation. Nevertheless it continued to increase, outweighing any other aspect of their deployment (Blatchford et al ., ; Trent, ). Rose and O’Neill () proposed that;
It is evident from the data that many [TAs] now perceive themselves to be part of a teaching partnership engaged in collaboration with teachers on a range of pedagogical activities.
…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, ‘exercising agency to contest their positionings within schools is often insufficient to place [LSAs] on a trajectory towards becoming a teacher’ (Trent, , p. 28). Rather, as reflected in this research, change comes through happenstance, talent spotting and peer or management encouragement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are viewed as "not quite teachers" (Edmond & Hayler, 2013, p. 216) leading to an ambiguous and conflicted identity. Role confusion is a factor because of the increase in numbers of assistants performing more complex duties in the classroom (Trent, 2014). This increase in teaching assistant roles is considered one of the most "profound educational changes" (Trent, 2014, p. 29) in recent years.…”
Section: Ericksonmentioning
confidence: 99%
“…This is not an uncommon experience for paraprofessionals in other disciplines, notably, teacher assistants. Studies of teacher assistants also indicate identity confusion because of insecurities between teachers and teacher assistants-the historically superior and subordinate positions lead the way for role ambiguity and role conflict (Edmond & Hayler, 2013;Trent, 2014).…”
Section: Work Relationshipsmentioning
confidence: 99%